2023
DOI: 10.1051/e3sconf/202342701022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the Effects of Waste Glass Powder Mixed with Hydrated Lime on the Unconfined Compressive Strength of Clayey Soil

Asmaa G. Salih,
Ahmad S. A. Rashid,
Nihad B. Salih

Abstract: Stabilization of clayey soil is commonly used to enhance unfavorable engineering properties. The effects of silica additives on soil improvement have been considered recently, and documented research studies on the characteristics of problematic clays stabilized by silica additives are interesting for many researchers. Alternative waste disposal strategies that would be both economically beneficial and environmentally friendly have been identified by this study. In the present study, waste silica-based additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…The use of PC ash facilitated aggregation and cementation within the clay fines, which contributed to significant changes in plasticity and thus a reduction in the compressibility behavior of the treated soils. The drastic reduction in compressibility characteristics found in this study is consistent with the results reported in studies conducted by Sharo et al (2022) and Salih et al (2023). A notable trend was observed wherein a decrease in Cc, Cr, and Sp was accompanied by an increase in σp for PC ash additions of 3%, 5%, 7%, and 10%, respectively.…”
Section: One-dimensional Consolidationsupporting
confidence: 91%
“…The use of PC ash facilitated aggregation and cementation within the clay fines, which contributed to significant changes in plasticity and thus a reduction in the compressibility behavior of the treated soils. The drastic reduction in compressibility characteristics found in this study is consistent with the results reported in studies conducted by Sharo et al (2022) and Salih et al (2023). A notable trend was observed wherein a decrease in Cc, Cr, and Sp was accompanied by an increase in σp for PC ash additions of 3%, 5%, 7%, and 10%, respectively.…”
Section: One-dimensional Consolidationsupporting
confidence: 91%